2015
DOI: 10.1002/14651858.cd011094.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Omega 6 fatty acids for the primary prevention of cardiovascular disease

Abstract: We found no studies examining the effects of either increased or decreased omega 6 on our primary outcome CVD clinical endpoints and insufficient evidence to show an effect of increased or decreased omega 6 intake on CVD risk factors such as blood lipids and blood pressure. Very few trials were identified with a relatively small number of participants randomised. There is a need for larger well conducted RCTs assessing cardiovascular events as well as cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 151 publications
2
37
1
1
Order By: Relevance
“…This finding has previously been observed in a meta-analysis [31]. The finding of lower levels of n-6 PUFAs in morbidly obese could be of clinical interest since the n-6 PUFAs have been considered pro-inflammatory [32], but no clear relationship with risk of cardiovascular disease has been demonstrated [33]. In the current study the levels of n-6 PUFAs remained unchanged, in contrast to the findings of Chalut-Carpentier et al who demonstrated a reduction in n-6 PUFAs 6 months after bariatric surgery [26].…”
Section: Discussionsupporting
confidence: 62%
“…This finding has previously been observed in a meta-analysis [31]. The finding of lower levels of n-6 PUFAs in morbidly obese could be of clinical interest since the n-6 PUFAs have been considered pro-inflammatory [32], but no clear relationship with risk of cardiovascular disease has been demonstrated [33]. In the current study the levels of n-6 PUFAs remained unchanged, in contrast to the findings of Chalut-Carpentier et al who demonstrated a reduction in n-6 PUFAs 6 months after bariatric surgery [26].…”
Section: Discussionsupporting
confidence: 62%
“…However, disagreement with the studies included in these analyses and others prompted Al-Khudairy et al [39] and Hamley [9] to conclude that replacing SAFA with mostly n-6 PUFA is unlikely to reduce CHD events or mortality. In contrast, Sacks et al [10], on behalf of AHA, concluded from 4 well-controlled RCTs that lowering the intake of SAFA and replacing it with unsaturated fats, especially PUFA, reduced CHD by about 30% and would lower the incidence of CVD.…”
mentioning
confidence: 98%
“…LA (n‐6 PUFA) and ALA (n‐3 PUFA) are essential fatty acids and are physiological and metabolically distinct . N‐6 PUFA play a vital role in many physiological functions but there was still controversy concerning about its effect on CVD risk . Dietary guidelines in many countries included a recommendation to consume oily fish, mainly on the basis of evidence from prospective cohort studies that fish consumption was cardioprotective .…”
Section: Discussionmentioning
confidence: 99%